“Treatment is both psychological and medical”: applying mixed methods to the understanding of mental and behavioral health in pediatric specialty medicine - Williford, Desireé N.; Kelleher, Jennifer; Davidov, Danielle M.; Duncan, Christina L. (Frontiers in Pediatrics, 2025)
IntroductionMental and behavioral health (MBH) access varies in pediatric specialty medicine and rural healthcare. This study aimed to characterize healthcare professionals' perceptions and experience with MBH services and readiness for change.MethodsThirty rural healthcare professionals completed validated questionnaires and semistructured interviews designed to meet study objectives. A convergent mixed methods design with a comparison method of interpretation was followed.ResultsThematic analysis yielded three major themes highlighting the prevalence of MBH concerns in practice, global perceptions of MBH care, and related barriers/facilitators to implementation. Current levels of MBH integration varied though overall readiness for change was high.DiscussionFindings highlight stakeholder perceptions about the role of MBH in pediatric specialty medicine. Key considerations for those who utilize or plan to adopt integrated MBH care at various levels are discussed, including readiness to change and other structural (e.g., organizational) or individual factors serving as facilitators and barriers to implementation.